God and Nature in the Old Testament - McKenzie, John L. (1963)
spez. 87-90: Nature in Ancient Near Eastern Religions; 100-101: Creation in Ancient Religious Myths; 110-114: Collision of Hebrew and Canaanite Beliefs; 114-116: Fertility and Divine Kingship.